CORRELATION BETWEEN PHYSICAL ACTIVITY AND BODY COMPOSITION CHANGES IN ADULT WOMEN (Physical Culture and Sport: Scientific Perspective, 2025)
Overweight and obesity are a major public health problem and their management is a key objective of health and fitness programs. Physical activity is considered a key component in combating obesity, overweight and improving body composition. This paper investigates the correlation between exercise and changes in body composition in overweight and obese adults, focusing on the impact of exercise on fat mass reduction and muscle mass gain. Objectives: to study the relationship between physical activity and changes in body composition; to evaluate the effects of different types of exercise on adults with obesity: to measure physical and body composition progress in a training program. The hypothesis of this paper hypothesizes that regular physical activity exerts a significant impact on changes in body composition in adults with obesity, facilitating a reduction in body fat percentage and promoting an increase in muscle mass. These changes would contribute to an overall improvement in physical fitness and metabolic parameters, supporting the effectiveness of therapeutic interventions in treating obesity. The aim of this study is to analyze the relationship between physical activity and changes in body composition in overweight and obese adults in order to identify the most effective physical exercises for reducing body weight. The study involved women aged 30 to 39 years, with a general health condition without serious illnesses, an average level of physical fitness, swimming skills, a desire to attend 2 classes per week, signing an informed consent, and consent to be evaluated before and after the program. The results of the study were analyzed and the most effective physical exercises for weight loss were determined.
Keywords: correlation; physical activity; body composition; women; overweight; obesity